CANDI SINGOSARI SEBAGAI SUMBER PEMBELAJARAN IPS - Nabhanuddin, Ilham; Ni'mah, Khoirun (Jurnal Penelitian dan Pendidikan IPS, 2024)
This research aims to show how Singosari Temple can be used as an interesting and effective resource in teaching social studies material, as well as increasing students' understanding of the importance of preserving historical and cultural heritage. This study uses descriptive qualitative type research. Data collection techniques: participatory observation and interviews with conservationists at Singosari Temple Malang. Data analysis techniques include thematic analysis and descriptive analysis. The results of the study show that Singosari Temple has proven to have great potential to be used as an interesting and effective learning resource in teaching social studies material, especially in the topic of Indonesian history and culture. The conclusion of the study explains that the use of historical sites such as Singosari Temple in social studies education can be an effective strategy to strengthen the sense of nationalism, deepen historical understanding, and foster awareness of the importance of preserving